The time-area fishing closure impacts on fish stock; Qiantang River before and after a four-month fishing closure - Aiju Zhang (Pensoft Publishers, 2021)
Fishing closures, commonly used to manage fisheries’ catch, involve temporarily closing a body of water to particular fishing gears to control fishing effort and protect feeding and spawning areas. In recent years in Qiantang River of China, with the socio-economic development, protection of fish stock has become increasingly urgent. The year 2019 was the first year that Qiantang River was included in the unified fishing ban system for the south of Yangtze River basin. Here, fish captures and hydroacoustic surveys were carried out in the research area of Qiantang River in order to present comparative descriptions of the dominant fish species, the temporal changes of fish size, density, biomass, and distribution affected by the four-month fishing closure in 2019. The results showed that Pseudobrama simoni (Bleeker, 1864) was the most dominant species both before and after the closure by using the traditional capture method. The mean target strength (TS) of overall fish after closure was –50.28 ± 0.19 dB, which was lower than that before, resulting in a significantly shorter derived mean length (13.42 ± 0.74 cm). The mean fish density and calculated biomass after closure were both significantly higher than that before it. More than 50% of fish species were distributed in the water of 5–20 m depth after the closure, which likely occurred in water deeper than 20 m before. Meanwhile, fewer outliers were found in different depth categories after closure. It is concluded that the four-month closure in 2019 had a positive effect on fish size, density, and biomass, leading to protection of pelagic fishes and a more even distribution of fish.